The Stages of Grief and Response of Cameron Turner in Confronting Death depicted in Benjamin Cleary's Swan Song - Bima Ardyandika; Destary Praptawati (J-Lalite: Journal of English Studies, 2023)
The underlying theory of grief is rooted in understanding the concept of loss. Stages of grief define the journey of accepting the reality of loss. Elisabeth Kübler-Ross shows these stages of grief by interviewing a terminally ill patient who was confronting the end-of-life transition. Stages of grief consist of denial, anger, bargaining, depression, and acceptance. Throughout the end-of-life transition, some may have a different response to grief at certain stages. This study aims to identify the stages of grief and the response to grief that Cameron Turner, the Swan Song film's main character, portrays. The data analysis exercises the qualitative descriptive method. The steps were watching the film and reading the script, identifying the data, classifying the data, reducing the collected data from the film and script, and analyzing the data. The findings of this study show that Cameron Turner was going through a complete grief stage of denial, anger, bargaining, and depression down to the acceptance stage. To respond to each stage, Cameron had a variety of modes of expression that differed in each of the stages of grief, such as verbal response, nonverbal response, physical response, and physical activities